RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN ROSELLA (HIBISCUS SABDARIFFA L) DENGAN PERLAKUAN PUPUK KANDANG KAMBING DAN KALIUM - IRAWATY ROSALYNE (JURNAL ILMIAH SIMANTEK, 2021)
The study used a randomized group design (RAK) factorial, with two treatment factors where the first factor is the provisionof goat manure consisting of 3 dose levels, namely O1: 8,000 kg / ha (7,200 gr / plot), O2: 10,000 kg / ha (9,000 gr / plot),O3: 15,000 kg / ha (13,500 gr / plot). The second factor is the administration of potassium fertilizer (KCL) consisting of 3dose levels, namely K1: 50 kg / ha (45 gr / plot), K2: 100 kg / ha (45 gr / plot), K3: 150 kg / ha (135 gr / plot). The parametersobserved in this study include: plant height (cm), number of branches (fruit), flowering speed (day), fresh weight of flowers(gr) and dry weight of flowers (gr). O3 goat manure treatment shows the highest plant height of 8 MST (165.35 cm), numberof branches (5.02 pieces), flowering speed (69.11 days), fresh weight of flowers (148.80 gr), dry weight of flowers (65.11 gr).The treatment of potassium fertilizer K3 = 150 kg / ha (135 gr / plot) shows the highest plant height (164.35 cm), number ofbranches (4.70 pieces), flowering speed (74.44 days), fresh weight of flowers (138.43 gr), dry weight of flowers (62.46 gr).The interaction treatment of goat manure and potassium fertilizer showed the highest plant height of 8 MST (169.39 cm),number of branches (5.61 pieces), flowering speed (83.33 days), fresh weight of flowers (152.72 gr), dried weight of flowers(45.56 gr).